2012
DOI: 10.1007/s00122-012-1953-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated consensus genetic and physical maps of flax (Linum usitatissimum L.)

Abstract: Three linkage maps of flax (Linum usitatissimum L.) were constructed from populations CDC Bethune/Macbeth, E1747/Viking and SP2047/UGG5-5 containing between 385 and 469 mapped markers each. The first consensus map of flax was constructed incorporating 770 markers based on 371 shared markers including 114 that were shared by all three populations and 257 shared between any two populations. The 15 linkage group map corresponds to the haploid number of chromosomes of this species. The marker order of the consensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 112 publications
(208 reference statements)
6
97
0
1
Order By: Relevance
“…Previously, the development of flax SSR markers had mainly been based on expressed sequence tags (EST) (Cloutier et al, 2009, 2012a), but more recently, genomic SSR markers have been found to be the most polymorphic markers in flax (Cloutier et al, 2012b). In agreement with more recent results, this study demonstrated that the value of Nei's gene diversity per locus for genomic SSRs in flax was higher than that for EST–SSRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the development of flax SSR markers had mainly been based on expressed sequence tags (EST) (Cloutier et al, 2009, 2012a), but more recently, genomic SSR markers have been found to be the most polymorphic markers in flax (Cloutier et al, 2012b). In agreement with more recent results, this study demonstrated that the value of Nei's gene diversity per locus for genomic SSRs in flax was higher than that for EST–SSRs.…”
Section: Discussionmentioning
confidence: 99%
“…SSRs are short, tandemly repeating nucleotide motifs (1–6 bp long) that are widely distributed in genomes of eukaryotic organisms genomes including flax (Tautz, 1989; Temnykh et al, 2001). The abundance, highly polymorphic nature, heritability, distribution, reproducibility and generally co-dominant nature of SSR markers make them highly suitable for MAS and genetic diversity studies (Wiesner et al, 2001; Cloutier et al, 2011, 2012b; Soto-Cerda et al, 2011a; Kumar et al, 2015; Kessuwan et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…PCR primers for SSR profiling were used as mentioned in Cloutier (2012). PCR amplification were carried out with initial denaturation step at 95°C for 5 min followed by later denaturation of 35 cycles for 30 sec at 95°C, primer annealing at 52°C for 30 sec, and extension at 72°C for 1 min.…”
Section: Genomic Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
“…In order to develop unique identity of trait specific germplasm SSR profiling of early flowering and maturing accessionsIC0096539 and IC0096496 was done using genetically mapped SSR markers (Cloutier 2012). Nine SSR primer pairs were screened for the identified accessions along with reference variety, Kota barani.…”
Section: Genomic Dna Extraction and Pcr Amplificationmentioning
confidence: 99%
“…Finally, the DNA was diluted to 5 ng/ll for PCR analysis. A set of 50 random SSRs, of which 24 were mapped SSRs from Cloutier et al (2012a) and rest 26 random SSRs developed from genomic sequences of linseed, were used for genotyping of the 168 accessions. The SSR primers were synthesized with an additional 18 base tag (5 0 -TGTAAAACGACGGCCAGT-3 0 ) at 5 0 end to all the forward primers (named as M13 tag) following Schuelke (2000).…”
Section: Genotyping With Ssrsmentioning
confidence: 99%